The colour stability of crystallized acetyl resin material in comparison to other restorative materials. An in-vitro study - Sarah Aburaisi; Abdulkarim Basha; Khalid Al Najjar; Husam Al Saqat; Faisal Al Askar; Fareed Al Nazer (Nature Publishing Group, 2021)
Abstract Aim To investigate the colour stability of Crystalized Acetyl Resin, in comparison to three other aesthetic restorative materials, when immersed in different staining aqueous solutions. Materials and methods Fifteen disc-shaped specimens each, of the four materials tested, were immersed in either DW or 4 staining solutions. CIE L*a*b* values were recorded using a digital spectrophotometer on a weekly basis for 4 weeks. Data were compared using three- way/two-way ANOVA along with auto-regressive model. Results Two-way Anova indicates that there is a significant colour change in all materials over time when immersed in the different staining solutions. Auto-regressive model showed that the colour change in each successive week was statistically significant (P < 0.001). Conclusion The most staining solution affecting the materials during this study was black coffee. Within the limitation of this study, Acetyl Resin was the most colour stable material among the other materials.